2015
DOI: 10.1016/j.neuroimage.2015.01.041
|View full text |Cite
|
Sign up to set email alerts
|

Central artery stiffness, baroreflex sensitivity, and brain white matter neuronal fiber integrity in older adults

Abstract: Cerebral hypoperfusion elevates the risk of brain white matter (WM) lesions and cognitive impairment. Central artery stiffness impairs baroreflex, which controls systemic arterial perfusion, and may deteriorate neuronal fiber integrity of brain WM. The purpose of this study was to examine the associations among brain WM neuronal fiber integrity, baroreflex sensitivity (BRS), and central artery stiffness in older adults. Fifty-four adults (65±6 years) with normal cognitive function or mild cognitive impairment … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
49
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 47 publications
(53 citation statements)
references
References 62 publications
4
49
0
Order By: Relevance
“…This hypothesis is supported by the present work using DTI in a young adult sample, wherein we found continuous associations between CFPWV and microstructural WM injury in several tracts (particularly the corpus callosum) that have been reported to be affected in elderly people with Alzheimer disease 29 . Our finding also extends observations from a recent tract-based spatial statistic DTI study 3 that identified similar associations in a sample of 55 older individuals. Despite the fact that voxel-based and tract-based studies are two methods using a fairly different approach, the prior study and the current data both identified the corpus callosum, corona radiata and internal capsule as regions that are particularly vulnerable to increased aortic stiffness.…”
Section: Discussionsupporting
confidence: 89%
See 2 more Smart Citations
“…This hypothesis is supported by the present work using DTI in a young adult sample, wherein we found continuous associations between CFPWV and microstructural WM injury in several tracts (particularly the corpus callosum) that have been reported to be affected in elderly people with Alzheimer disease 29 . Our finding also extends observations from a recent tract-based spatial statistic DTI study 3 that identified similar associations in a sample of 55 older individuals. Despite the fact that voxel-based and tract-based studies are two methods using a fairly different approach, the prior study and the current data both identified the corpus callosum, corona radiata and internal capsule as regions that are particularly vulnerable to increased aortic stiffness.…”
Section: Discussionsupporting
confidence: 89%
“…1, 26 In particular, the association between central artery stiffness and WMH burden has been frequently and consistently reported among older individuals 3, 4, 27 . In the FHS Offspring cohort of older individuals, recent findings suggest that only CFPWV and MAP are associated with WMH burden.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Consistently, our recent study also demonstrated that aortic stiffening and blunted cardiovagal baroreflex sensitivity are associated with reductions in brain neuronal fiber integrity and executive function performance in older adults (Tarumi et al . ). Nevertheless, the potential causal effect of arterial stiffening or blunted baroreflex sensitivity on cognitive impairment requires further research, and it should also be kept in mind that brain neurodegenerative disease per se may impair the baroreflex function.…”
Section: Age and Cbf Oscillationmentioning
confidence: 97%
“…11 The consistent loss of smooth muscle cells and presence of arteriolar injury have the functional consequences of impaired autoregulation, with incapacity to accommodate alterations of systemic blood pressure. 14,15 …”
Section: Vascular Source Of Microbleeds: Arterioles and Capillariesmentioning
confidence: 99%